Pulling strength with pinch grips: A variable for product design - Razza, Bruno Montanari [UNESP]; Paschoarelli, Luis Carlos [UNESP]; Silva, Danilo Corrêa [UNESP]; Ulson, José Alfredo Covolan [UNESP]; Lucio, Cristina do Carmo [UNESP] (My University, 2012)
Pulling with pinch grips is an action frequently used in either occupational or daily living activities, especially in situations where the object is too small, the access to the object is restricted, the use of tools is prevented and situations such as pulling strips out of long-life packaging, removing seals from flask lids, tearing a plastic bag, etc. Excessive demands of strength in those actions may limit the user’s access to certain activities and even lead to injury. The objective of this study was to collect valid data of pulling strength with pinch grips to be applied to the design of safer and more comfortable products and tasks. Three handles of different heights (1 mm, 20mm and 40mm) were used in the study and three types of pinch grips were measured with both hands: pinch-2, chuck pinch and lateral pinch. The study included 30 men and 30 women, all right-handed and healthy, and the maximum voluntary isometric contraction was measured in the standing posture. The results showed that the type of pinch grip used influenced more greatly the pulling strength than the size of the handles. This study provides biomechanical data of an action often performed in many daily living activities and also in several occupational tasks, but has been still little explored.
Keywords: Biomechanics; Ergonomic design; Isometric strength; Pinch grip; Pulling strength